The features of the growth of Crataegus ucrainica (Rosaceae) on the Shelestiv island in the floodplain of the Dnipro river (Kaniv Natural Reserve) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The existing features of Crataegus ucrainica A. Pojark in the floodplain of the Dnipro river (Shelestiv island) are investigated. This habitat includes 14 individuals (20–25 years old) of C. ucrainica. It is located opposite the more mature population (55–60 years old) which was discovered at the mouth area of the Ros’ river earlier by authors. Three soil profiles around 2 meters deep were dug out in the descent places of dried straits. For two profiles located in close proximity to the C. ucrainica individuals, the location of two or three loams and clays stratums of varying thickness at different depths was founded. These stratums provides existence of this species on the alluvial sands array. In the third profile, which was located in the same conditions, but without the presence of C. ucrainica, the shallow waterproof stratums were not detected. Coenotically investigated vegetation groups of these localities are classified as Salicetea purpurea Moor 1958. Coenotic conditions of the habitat of this species in the mouth area of the Ros’ river are similar. Investigated location exists in the absolute reserve regime. This habitat is good model for observing the conservation of the population and organizing long-term monitoring of its development.
Keywords: rare species, flood plain island, Middle Dnipro area, protection.